Changing on the Fly : Hockey through the Voices of South Asian Canadians - Szto, Courtney (Book collections on Project MUSE., 2021)
"Hockey and multiculturalism are often noted as defining features of Canadian culture; yet, rarely are we forced to question the relationship and tensions between these two social constructs. This book examines the growing significance of hockey in Canada's South Asian communities. The Hockey Night in Canada Punjabi broadcast serves as an entry point for a broader consideration of South Asian experiences in hockey culture based on field work and interviews conducted with hockey players, parents, and coaches in the Lower Mainland of British Columbia. This book seeks to inject more "color" into hockey's historically white dominated narratives and representations by returning hockey culture to its multicultural roots. It encourages alternative and multiple narratives about hockey and cultural citizenship by asking which citizens are able to contribute to the webs of meaning that form the nation's cultural fabric"--